The larva of Plectrocnemia scruposa McLachlan 1880 (Trichoptera, Polycentropodidae - Waringer, Johann; Graf, Wolfram (Zootaxa, 2020)
This paper describes the previously unknown larva of Plectrocnemia scruposa McLachlan 1880. Information on the morphology of the 5th larval instar is given, and the most important diagnostic features are illustrated. In the context of existing identification keys, P. scruposa keys together with P. brevis McLachlan 1871, P. conspersa (Curtis 1834), and P. laetabilis McLachlan 1880. These species can be separated by the length of the outermost seta of the posterolateral trio on the last abdominal tergum and by presence/absence of a central pigmented mark on the posterior margin of the labrum. According to mandible morphology, the larva of this species appears to be mainly a predator and passive filter feeder of particulate organic matter.